Effect of initial curing conditions on the durability performance of low-calcium fly ash-based geopolymer mortars - Yilmaz, Arin; Degirmenci, Fatma Nurhayat; Aygoermez, Yurdakul (ELSEVIER, 2024)
Geopolymer composite production has become an indispensable product to reduce carbon dioxide emissions, which have become an important problem today, and to provide green sustainability. Concerns about the global climate change problem have also accelerated geopolymer studies. This research investigated the mechanical and durability characteristics of low-calcium fly ash (LCFA) based geopolymer mortars with different curing temperatures and times. Two forms of curing conditions were applied; the first one was standard curing at room temperature (20 +/- 3 degrees C and RH 65 +/- 10%) and the second one was cured in the hot air at 40 degrees C, 60 degrees C, and 80 degrees C for 24 h, 48 h, and 72 h followed by standard curing. After all curing processes, compressive strength, flexural strength, water absorption, void ratio, resistance to elevated temperatures, and freeze-thaw conditions were determined experimentally. In addition, SEM analysis was performed before and after durability tests for comparison purposes. Also, XRD and TGA analyzes were performed. According to test results, curing specimens at longer times and higher temperatures has been shown to increase compressive strength results. The highest compressive strength value was reached at 80 degrees C degrees C after 72 h of curing. Geopolymer specimens subjected to elevated temperatures (600 degrees C and 900 degrees C) lost a significant part of their strength value. After the freeze-thaw test, LCFA-based geopolymer specimens showed more than 70% resistance. The freeze-thaw resistance of geopolymer samples was positively affected on long-term curing at high temperatures, but high-temperature resistance was impacted negatively. (c) 2023 The Authors. Published by Elsevier Espa na, a, S.L.U. on behalf of SECV. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/ by-nc-nd/4.0/).
Keywords: Geopolymer mortar; Fly ash; Heat curing; Compressive strength; High-temperature resistance; Freeze-thaw resistance; FREEZE-THAW; TEMPERATURE; STRENGTH; RESISTANCE; DURATION; CONCRETE; Materials Science